(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
For the first time the presence of Chionea araneoides (Dalman), previously known in northern Europe, has been recorded on the Italian Alps. Research has proven, by studying the chetotaxis and copulatory organ of the male in comparison with the C. minuta (Lund.), that morphologically there is a clear distinction between the two species. Finally, a classification key of the species of Chionea Dalman at present known in Italy is given.